A tribological model for geometrically structured anisotropic surfaces in a covariant form. (30th March 2020) - Michaloudis, G.; Konyukhov, A.; Gebbeken, N.
Abstract: This contribution proposes a tribological model within a three‐dimensional contact formulation considering structural anisotropy of the contact interface. A simple elastoplastic constitutive law is adopted for the description of the behavior on the anisotropic contact interface. Starting with the establishment of the thermodynamic framework of the contact problem, the dissipative, irreversible process is described. By applying the principle of maximum dissipation, the evolution equations and the expressions of the tangential contact forces for the cases of sticking and sliding are obtained and, subsequently, formulated in algorithmic form, in order to enable their implementation into finite element codes. The anisotropic behavior is incorporated through the definition of a tensor of anisotropy. The form of this tensor is defined in a general curvilinear coordinate system. The cases of both constant and nonconstant anisotropic tensor are studied. The analytical solution of a numerically computed problem, serves the validation of the proposed model.